University of the Future (UotF): redesign business model for local university in Malaysia through humanising education and 4IR - Yahaya, Nor Zaiasron; Ahmad Dahlan, Abdul Rahman (International Journal of Science and Research (IJSR), 2019)
This paper describes a process to redesign business model on local university in Malaysia. This redesign purpose is to build thelocal university of the future (UotF) model in Malaysia. Recently this new (UotF) design is one of the new business model process which is going to be in Malaysia. This (UotF) business model is highly in demand in higher education environment and thedevelopment process is concurrently with the information technology revolutionespecially on the concept of smart digital campus strategy.Besides this paper also providesmethodology approach towards redesign the university business model for the UotF. Additionally it provides some explanation on the concept of Fourth Industrial Revolution (4IR), Business Model Canvas (BMC)and Value Proposition Canvas (VPC) to one of the local universities in Malaysia that can be related through the humanizing education in future.